2017
DOI: 10.1017/thg.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Post-Traumatic Stress Disorder in Two High-Risk Populations

Abstract: Mexican Americans and American Indians constitute conspicuously understudied groups with respect to risk for post-traumatic stress disorder (PTSD), especially in light of findings showing racial/ethnic differences in trauma exposure and risk for PTSD. The purpose of this study was to examine genetic influences on PTSD in two minority cohorts. A genome-wide association study (GWAS) with sum PTSD symptoms for trauma-exposed subjects was run in each cohort. Six highly correlated variants in olfactory receptor fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…For example, it has been well-established that the profile of ASD symptoms varies greatly across cultures, especially with regard to the symptom cluster of dissociation [ 36 ]. Furthermore, the disparity of genetic background across ethnicities may have played a role in the different pooled prevalence observed across countries [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been well-established that the profile of ASD symptoms varies greatly across cultures, especially with regard to the symptom cluster of dissociation [ 36 ]. Furthermore, the disparity of genetic background across ethnicities may have played a role in the different pooled prevalence observed across countries [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most GWAS test hundreds of thousands to several million SNP variants, with the requirement that this large number of genetic features would need a large number of samples. Some of the current and most successful human GWAS in PTSD are summarized in Table 1, in which 11 genome-wide studies are reported in chronological order [12••, 39, 40, 41•, 42, 43•, 44•, 45•, 46•, 47, 48]. SNP identification numbers and nearest genes are also recorded together with the sample sizes and the ancestry breakdown.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…In standard GWAS, the level of probability needed to reach “genome-wide significance” is simply the standard alpha = 0.05 divided by the approximate number of tests (~ 1,000,000 SNPs), for a derived multiple testing value of significance at p <5× 10 −8 . The majority of studies in Table 1 met genome-wide significance, except Wolf et al 2014, which was a GWAS focused on dissociation [42]; Kilaru et al [47], which used a different type of gene-based analysis, and thus arguably may not be required to meet the same GWAS level of statistical correction (since they were testing approximately 40,000 genes instead of 1 million SNPs); as well as Ashley-Koch et al [45] and Melroy-Greif et al [48]. …”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…These conditions are not unlike those which have deprived minority Black populations of access to economic and social resources for many decades and multiple generations (Dymski & Mason, 2005). Although lifetime experiences of trauma and post-traumatic stress have been associated with behavioral health risks in Hispanic populations (Ehlers et al, 2016; Melroy-Greif, Wilhelmsen, Yehuda, & Ehlers, 2017), these effects are magnified and maintained–affectively and perhaps genetically–in populations for whom large-scale major traumas continue to be experienced across generations, as historical trauma (Ehlers, Gizer, Gilder, Ellingson, & Yehuda, 2013; Nutton & Fast, 2015; Soto, Baezconde-Garbanati, Schwartz, & Unger, 2015; Sule et al, 2017; Truesdale-Moore, 2017). Recent research links “historical trauma” to changes in DNA methylation (so-called epigenetic changes) (Aguiar & Halseth, 2013; Brockie, Heinzelmann, & Gill, 2013), although among American Indians and Alaska Natives this research may be limited by indigenous people’s understandable reluctance to provide tissue for such analyses (Lock, 2015).…”
Section: Discussionmentioning
confidence: 99%